New languages of schooling: Ethnicity, education, and equality in Nepal - Pradhan, U (Association for Nepal and Himalayan Studies, 2016)
Mother tongue education has remained a controversial issue in Nepal. Scholars, activists, and policy-makers have favored mother tongue education from the standpoint of social justice. Against these views, others have identified this effort as predominantly groupist in its orientation and not helpful in imagining a unified national community. Taking this contention as a point of inquiry, this paper explores the contested space of mother tongue education to understand the ways in which people position themselves within the polarizing debates of ethnicitybased claims on education in Nepal. Drawing from the ethnographic fieldwork in a mother tongue education school, I illustrate that the students made meaning in their everyday world by maintaining the multilingual repertoire that included their mother tongue, Nepali, and some English; multilingualism was used as a strategy for mother tongue education. I propose a notion of simultaneity to explain this attempt to seek membership into multiple groups and display of apparently contradictory dynamics. On the one hand, the practices in these schools display inwardlooking characteristics through the everyday use of mother tongue, the construction of unified ethnic identity, and cultural practices. On the other hand, outward-looking dynamics of making claims in the universal spaces of national education and public places could also be seen. The salience of these processes is the simultaneous membership to multiple groups, claims over public spaces and in the spaces of nationalism, hitherto associated with Nepali language. Contrary to the essentialist categories espoused in both nationalist discourse and ethnic activism, students in these schools display affiliation to multiple languages and identities that were seen as neither incompatible nor binary opposites.